Kelekatan Orangtua dan Kemampuan Kontrol Diri terhadap Perilaku Agresi Remaja - Ardianti Agustin; Fifin Dwi Purwaningtyas; Evi Ristanti; Yulinda Fira (Ilmu Psikologi Universitas Yudharta Pasuruan, 2022)
Adolescence is a stage of development where various behaviors appear, one of which is aggressive behavior. This is an important issue because aggressive behavior can harm the environment and other people, both physically and psychologically. Things that may determine the emergence of aggressive behavior in adolescents are the quality of parental attachment and self-control. The purpose of this study was to examine the relationship between the quality of parental attachment and self-control with aggressive behavior in adolescents. This study uses 3 variables, namely parental attachment and self-control is the independent variable and aggressive behavior is the dependent variable. The population in this study were late teens, the sample used was purposive sampling. This research uses multiple linear regression analysis methods. The results showed that the calculated Fvalue = 50,634 > Ftable = 2.59 (p = 0.000 <0.05), meaning that there was a significant relationship between the quality of parental attachment and self-control with adolescent aggressive behavior. Parental attachment and aggressive behavior gave an effective contribution of 5.91% while the contribution of self-control to aggressive behavior was 20.77% so that self-control had a more dominant influence on adolescent aggressive behavior. Aggressive behavior is influenced by other factors of 73.3% which were not examined by researchers.